Note - Lindsay, H. Scott
010-0038-001 23.11.36 Scott Lindsay says that the Parliamentary L.P. Executive are meeting the French delegation at 6pm tonight (Monday) He says that their information is that the delegation is here with the authority of Blum. B. 292/946/10/40